Extended-Spectrum Beta-Lactamases - Kevin R Forward (Canadian Journal of Infectious Diseases and Medical Microbiology)
The definition of extended-spectrum beta-lactamases (ESBLs) has expanded rapidly, in terms of both the number and the variety of enzymes. Bacteria bearing plasmidic ESBLs are spreading widely throughout the world. In Canada, the problem has grown less rapidly than in other parts of the world; however, ESBLs still present a significant impediment to the treatment of serious infections with extendedspectrum cephalosporins and penicillins. Although SHV-derived enzymes were the primary concern in the late 1980s and early 1990s, these enzymes have been rapidly overtaken by the CTX-M family of ESBLs. There is no reason to believe that the problem of ESBLs will not expand rapidly in the face of intense antimicrobial pressure and lapses in infection control practices. Control should focus on early detection, accurate characterization, effective treatment and measures to prevent further spread.